Utilization of Local Resource Feed For Balinese Cattle - Ni Made Yudiastari; I Gusti Ayu Dewi Seri Rejeki; I Gusti Agus Maha Putra Sanjaya; Luh Suariani; I Nyoman Kaca; Ni Ketut Sri Rukmini; Ni Ketut Etty Suwitari; Ni Ketut Mardewi; I Gede Sutapa; Ni Made Ayu Gemuh Rasa Astiti; Yuminsia Neni; Sri Wulan Sundari (PT Inovasi Pratama Internasional, 2026)
This community service activity is carried out as a form of academic contribution to enhance the knowledge and skills of the community, especially the Kelompok Ternak Amerta Sari in Kesiut Village, in processing and preserving local resources as alternatives for livestock feed, particularly for Bali cattle. The issues faced by farmers in this area include limited availability of fresh feed, especially during the dry season, and the suboptimal use of local feed materials such as straw, turi leaves, and other agricultural waste. Through this activity, the service team provides training and guidance in feed processing techniques such as fermentation, silage, and the production of complete feed based on local resources. The methods used include counseling, technical demonstrations, and hands-on practice together with the farmer group members. The results of this activity show an increase in the understanding and skills of the community in preserving and processing livestock feed.